INCREASE THE USEFUL WORK COEFFICIENT OF PHOTOELEMENTS BY ACTIVE COOLING (British Journal of Global Ecology and Sustainable Development, 2023)
Several ways to increase the useful working coefficient of photoelements were studied and it was found that cooling us in conditions is the most effective method. Given that the factors that reduce the useful working coefficient of photoelements are dust and temperature, cooling the photoelements with water and washing the dust accumulated on the surface of the solar panel through manashu water has worked highly.